Hair cortisol, perceived stress, and social support in mother–child dyads living in an urban neighborhood. (2nd November 2019) - Hollenbach, Jessica P.; Kuo, Chia-Ling; Mu, Jinjian; Gerrard, Meg; Gherlone, Nicole; Sylvester, Franklin; Ojukwu, Mary; Cloutier, Michelle M.
Abstract: Women and children belonging to a racial/ethnic minority bear a disproportionate burden of psychosocial stress that increases their vulnerability to adverse health outcomes. Hair cortisol has been rapidly advanced as a biomarker of the intensity and course of the stress response over time and may provide an opportunity to increase our understanding of the role of psychological stress in health. However, research on the link between hair cortisol levels and subjective measures of maternal and child stress among low-income and minority individuals is limited. The goal of this study was to examine the association between stress and hair cortisol in low income, minority women and children who experience disproportionate exposure to chronic stress. A convenience sample of 54 minority mother/child dyads from a busy primary care clinic in the second poorest medium-sized city in the US participated in the study. Mothers self-reported perceived stress, social support, household characteristics and other demographic factors, and their children (ages 7–14 years) reported on the perceived level of safety in their neighborhood and exposure to violence as markers of child stress. Three-centimeter hair samples were collected from both mothers and children during the clinic visit, and hair cortisol levels were assessed via enzyme-linked immunosorbent assays. Linear regression models examined associations between maternal and child hair cortisol, and between hair cortisol and perceived stress level in women, and moderation by social support. Maternal hair cortisol was not significantly associated with mother's perceived stress. Maternal and child hair cortisol levels were positively associated ( p  = .007) but this association was not moderated by maternal perceived social support. These findings suggest that hair cortisol is strongly associated among this sample of minority mother–child dyads and is not moderated by social support.